2016
DOI: 10.1002/2015ja021784
|View full text |Cite
|
Sign up to set email alerts
|

Transport and chemical loss rates in Saturn's inner plasma disk

Abstract: The Kronian moon Enceladus is constantly feeding its surrounding with new gas and dust, from cryovolcanoes located in its south polar region. Through photoionization and impact ionization of these neutrals, a plasma disk is created, which mainly contains hydrogen ions and water group ions. This paper investigates the importance of ion loss by outward radial transport and ion loss by dissociative recombination, which is the dominant chemical loss process in the inner plasma disk. We use plasma densities derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…As new ions are produced by hot electron impact ionization the largest ion production rate, in the region close to the equatorial plane, will be found in between the maxima of the neutral density and the hot electron density. It should be noted that the equatorial plasma density peak does not correspond to the peak of the total flux tube content, which instead peaks around magnetic L shell 6.3 (Sittler Jr et al, ) and 6.6 (Holmberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As new ions are produced by hot electron impact ionization the largest ion production rate, in the region close to the equatorial plane, will be found in between the maxima of the neutral density and the hot electron density. It should be noted that the equatorial plasma density peak does not correspond to the peak of the total flux tube content, which instead peaks around magnetic L shell 6.3 (Sittler Jr et al, ) and 6.6 (Holmberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Assuming quasineutrality of the plasma disk, that is, n i ≈ n e ≈ n , for the steady state situation we get κ n n + k n eh n n = α e f f n 2 + n / t . Holmberg et al () showed that the dominant loss process in the plasma disk is transport loss, so for a rough estimate we use κ n n + k n eh n n = n / t .…”
Section: Resultsmentioning
confidence: 99%